On the maximum thermal load of ground heat exchangers - Kyriakis, Nikolas; Michopoulos, Apostolos; Pattas, Konstantinos (My University, 2006)
Ground heat exchanger (GHE) coupled heat pumps constitute an alternative system for the air conditioning of buildings, with the vertical U-tube type being the most popular. The installation cost and the overall performance of the system strongly depends on the designing and dimensioning, which however present significant difficulties. The critical parameter in designing vertical systems is the thermal power per meter of borehole that the GHE can handle. This paper presents a calculation algorithm, which aims to redefine the maximum thermal load allowable in vertical ground heat exchangers.
Keywords: Ground heat exchanger (GHE); Maximum loading of GHE; Heating; Cooling